IMPLEMENTASI KURIKULUM MERDEKA PADA PEMBELAJARAN BAHASA ARAB DI MADRASAH ALIYAH NEGERI 1 KENDARI - Nisa, Ainy Khairun; Al Ghifary, Mujahid (STIQ Amuntai, 2023)
Education is something that a person needs to gain useful knowledge and form a character with good morals. The implementation of the independent curriculum has been implemented optimally, but of course, the form of implementation is still being carried out in stages. This research aims to describe the implementation of the independent learning curriculum at MAN 1 Kendari, which is identical to religious subjects based on KMA 183 and KMA 184 in 2019. This research method uses a descriptive qualitative method, which explains something real by looking at the situation. Occurs and leads to direct activity. Research techniques use observation and interview techniques. The results of the research have identified that the implementation of the independent learning curriculum at MAN 1 Kendari has gone well. However, there is still a need for cooperation between students and teachers as well as all Madrasah parties to develop an independent learning curriculum that is already running. Motivation is needed from the school principal to be able to continue straighten out when there are mistakes in learning, especially in Arabic subjects.